THU0012 Regulatory T- Cells in Peripheral Blood of Dmard-Naive Patients with Very Early Rheumatoid Arthritis: Association with Disease Activity and Systemic Disease Manifestations. (15th July 2016) - Avdeeva, A.; Rubtsov, Y.P.; Dyikanov, D.T.; Popkova, T.V.; Aleksandrova, E.N.; Tkachuk, V.A.; Nasonov, E.L.
Abstract : Background: Regulatory T (Treg) cells play a critical role in the regulation of peripheral immune tolerance.The ability of Tregs to suppress T-cell responses, and thereby to regulate immune reactions, points to their key role in the pathophysiology of autoimmune diseases Objectives: To investigate the percentage and absolute number of Treg cells in peripheral blood of healthy donors and DMARD-naive very early rheumatoid arthritis (VERA) patients (pts) by immunocytometry and to analyze the association between Treg cells subsets and RA activity Methods: Peripheral blood of 20 healthy donors and 39 VERA DMARD-naive pts (34F/5M, Me;IQR age 50; 32–58 years, disease duration 5.0; 4.0–6.0 months, DAS28 5.1; 4.3–5.8, RF positive-66.7%, anti-CCP positive-87.2%) were assessed for Treg-cell subpopulations. Human blood mononuclear cells were isolated from whole venous blood by Ficoll–Hypaque centrifugation and subjected to multicolor flow cytometry analysis. Tregs were stained for different surface markers, and proportions of marker-positive subsets (FoxP3+CD25+; CD152+surface; CD152+intracellular; FoxP3+CD127-; CD25+CD127-; FoxP3+ICOS+; FoxP3+CD154+; FoxP3+CD274+) between healthy controls and pts were compared Results: We found the lower percentage of FoxP3+CD25+T-cells in pts with VERA, compared to healthy donors: 5.5% (4.1–6.5) vs 6.9% (5.8–7.9); the percentage and the absolute number of FoxP3+ICOS+T-cells: 6.9% (2.1–11.5) vs 10.8% (9.3–13.7); 0.0035 (0.0013–0.0067) vs 0.0068 (0.0039–0.009);the percentage and the absolute number of FoxP3+CD154+T-cells: 0.47% (0.19–0.83) vs 1.5% (1.12–2.08); 0.0002 (0.0001–0.0005) vs 0.0009 (0.0005–0.0014); the percentage and the absolute number of FoxP3+CD274+-cells: 0.6% (0.3–1.5) vs 1.9% (1.2–2.2); 0.0003 (0.0002–0.0007) vs 0.001 (0.0006–0.0016), p<0.05 for all cases. We found a negative correlation between the percentage of FoxP3+CD25+ T-cells and CRP in pts with VERA (r=-0, 4), ESR (r=-0, 43); the percentage of CD152+ intracellular T-cells and DAS28 (r=-0, 4), ESR (r=-0, 52), CRP (r=-0, 55); the percentage of FoxP3+CD127- T-cells and ESR (r=-0, 41), CRP (r= -0, 48); the percentage of CD25+CD127-T-cells and DAS28 (r=-0, 53), SDAI (r=-0, 5), CDAI (r=-0, 44), ESR (r=-0, 56), CRP (r=-0, 53), p<0.05 for all cases. Low percentage of CD25+CD127–cells compared to pts with low/moderate disease activity was observed in the group of pts with high disease activity (DAS28>5.1 SDAI>26 CDAI>22, n=27) (5.1% (4.9–5.6) vs 6.9% (6.4–7.9), p<0.05). A lower percentage of FoxP3+CD127- T cells: 4.2% (2.8–5.4) vs 6.4% (4.9–7.3) and the percentage of CD25+CD127- cells: 5.1% (3.5–5.1) vs 6.6 (5.6–7.9) was found in pts with systemic disease manifestations (n=7), p<0.05 for all cases Conclusions: VERA pts have demonstrated the lower frequency of FoxP3+CD25+regulatory T cells and the percentage and the absolute number of FoxP3+ICOS+, FoxP3+CD154+, FoxP3+CD274+ cells in comparison to healthy donors. These markers characterize activated Treg cells, capabale of effective immunosuppression, thus lower levels of these markers on Treg surface and reduced numbers of marker-positive cells, suggest that Treg function is reduced in VERA pts. Diminished T-reg cell counts are associated with higher disease activity and systemic disease manifestations Disclosure of Interest: None declared